TUGAS DAN FUNGSI DINAS KESEHATAN PROVINSI JAWA TENGAH BERKAITAN DENGAN PROGRAM JAMINAN KESEHATAN DAERAH ( JAMKESDA ) - Gilang Prama Jasa, Ratna Herawati*), Henny Juliani (Diponegoro Law Journal, 2013)
Law Number 32 Year 2004 on Regional Government Article 22 and Article 167 letter h have established regional obligations and expenditures priorotas to develop a social security system in this regard include guarantees for health services. It is therefore the responsibility as mandated by these regulations is positively captured by the Central Java Provincial Government to immediately improve health financing systems through the development of programs Jamkesda Central Java Province. Central Java Provincial Health Office is one of the institutions that support efforts to realize development and was instrumental in the organization of health Jamkesda Central Java Province. On the basis that the authors wanted to examine the duties and functions of the Central Java Provincial Health related Jamkesda Central Java program and the obstacles that occur.                       This legal research using normative juridical approach, the specification of descriptive analytical study. Data collection methods used are literature study that focuses on the primary legal materials and secondary legal materials.               From the results of this research note that there are four aspects of the duties and functions of the Central Java Provincial Health related Jamkesda program that includes aspects of the organization's Central Java Provincial Health Office as a member of the Executive Team Jamkesda Central Java province, the monitoring aspect of membership participation Jamkesda Java middle, financing aspects and aspects of health care. The barriers of Central Java Provincial Health Office in the performance of duties and functions related to program Jamkesda include external barriers and internal barriers that the dual role of the Central Java Provincial Health Office as a regulator and operational.                                                                    Support ideas from various stakeholders for program development Jamkesda Central Java Province is required. Since the development Jamkesda Central Java will not work when executed by one Unit (SKPD) only. Key to the success of this program is a shared responsibility that can ultimately be shared also by all the people, especially in the province of Central Java.